Legal Consequences For Foreign Guaranteers in Indonesia Who Do Violation - Muhammad Ivan Septian Islamsyah Ikmal; Siti Marwiyah; Subekti; Syahrul Borman (Universitas Islam Malang, 2023)
Every foreigner who holds a Visit Stay Permit, Limited Stay Permit, and Permanent Stay Permit is required to have a Guarantor who guarantees the existence and activities of guaranteed foreigners while in Indonesian Territory. The absence of detailed regulations and special legal protection for a guarantor has various impacts and consequences. One of them is the lack of responsibility of a guarantor. This research is legal research, which focuses on legal studies on positive law. The problem approach used is the philosophical approach, the statutory approach and the conceptual approach. primary legal materials in the form of laws and regulations relating to research problems and secondary legal materials, namely legal materials that provide explanations of primary legal materials, such as legal books, journals, published magazines relating to the problem. The results of the research show that the responsibility of a guarantor is to supervise and monitor the activities of the foreigners he guarantees in Indonesian territory, to be responsible for the presence and activities of foreigners while in Indonesian territory, Article 63 paragraph (2) of Law no. 6 of 2011, which confirms the guarantor's obligation to report if there is a change in civil status, immigration status and change of address or becomes the subject of immigration administrative action in the form of deportation, the guarantor's sanctions for violations are more administrative in nature. More severe criminal sanctions are often not carried out in law enforcement. Supposedly a foreigner who violates the provisions of Article 116, the guarantor can already be said to have violated the provisions of article 118 because he does not fulfill obligations related to the existence of the guaranteed foreigner.